A new species of Silvinichthys (Siluriformes, Trichomycteridae) lacking pelvic fins from mid‐elevation localities of the southern Andes, with comments on the genus - L. Fernández; E. A. Sanabria; L. B. Quiroga; R. P. Vari (Journal of Fish Biology, 2014)
Silvinichthys huachi new species, is described from a stream along the lower slope of the Andean Cordillera in the Provincia de San Juan, Argentina. It shares the distinctive modifications characteristic of Silvinichthys , but is distinguished from the four previously described congeners by the combination of a lack of the pelvic fin and the pelvic girdle, details of pigmentation and various meristic and morphometric features. Silvinichthys huachi is apparently endemic to the type locality situated within an arid region of western central Argentina in the Andino Cuyana Province. Major gaps in the range of species of Silvinichthys may indicate that the origin of the genus predates the uplift events that subdivided drainages along the eastern slopes of the Andean Cordillera in west central Argentina. Silvinichthys huachi is hypothesized to be the sister species of Silvinichthys bortayro .